MODEL OF ISLAMIC MONETARY OPERATION FOR LIQUIDITY MANAGEMENT IN ISLAMIC BANKING Case of Indonesia 2000-2009 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
The paper attempts to construct the model of islamic monetary operation for liquidity management in islamic banking. Particularly, the model investigates variables that determine the role of the central bank in managing liquidity. Firstly, it explores the related conventional models and chooses one to find general variables involved in monetary operations for managing liquidity. Secondly, it formulates the islamic model after considering the islamic monetary operation principles, characteristics of both islamic onetary instruments and Indonesian islamic banking industry. Specifically, it models Bank Indonesias islamic monetary instrument called Bank Indonesia Sharia Certificate (SBIS). Thirdly, the model points out that the volume of SBIS is influenced by reserves requirement, currency in circulation, and prior auctions of SBIS. It means that the application of islamic OMO is not significantly different from monetary instrument in conventional OMO. Therefore, the paper suggests the issuance of islamic investment monetary instruments to implement the ideal islamic monetary instrument and OMO.